Effect of ferulic acid on the performance of soy protein isolate-based edible coatings applied to fresh-cut apples - Alves, Maria M. (2017)
The economic importance of fresh-cut fruit market is becoming progressively more significant, while the food industry shows increased interest in innovation of products bringing health benefits. The objective of this work was to assess the potential of incorporating ferulic acid (antioxidant with reported bioactivity that can act as cross-linking agent) in soy protein-based edible coating formulations in order to increase the quality and shelf life of fresh-cut apples (cv. Golden). Glycerol was used as plasticizer and ferulic acid was incorporated in concentrations between 1.0 and 4.0 g L?1. The properties of fresh-cut apples were analysed during seven days of storage at 10 °C. A common commercial antioxidant (sodium ascorbate at 10 g L?1) was tested for comparison. Uncoated apples and apples dipped into antioxidants solution were used as controls. The results emphasized the need to incorporate this phenolic antioxidant in a biopolymer matrix, due to its hydrophobic characteristics and consequently a poor dispersion along the surface of the fruit. They also indicate that the efficiency of the coatings incorporating ferulic acid is highly dependent on pH. The formulation with ferulic acid at 4.0 g L?1 and pH 7.0 has demonstrated potential application in extending the shelf life of fresh-cut apples.